Exploring the Neuroprotective Effects of Mechanosensitive Channel Blocker, GsMTX4 in Intracerebral Hemorrhage Model in Rats - Liu, Wenyan; Zhang, Guiyu; Wang, Jin; Liu, Jing; Yuan, Yu; Hong, Jun; Ding, Yi (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The current study explored the usefulness of a mechanosensitive channel blocker, GsMTX4 in intracerebral hemorrhage (ICH)-associated deleterious effects along with the possible mechanisms. Materials and Methods: Type VII collagenase was administered in the right basal ganglia using stereotactic apparatus to induce ICH in rats. The ICH-associated injury was assessed using corner turn and forelimb placement tests (behavioral test); Evans blue extravasation test (blood-brain barrier damage), brain edema, apoptotic markers (caspase-3 and Bcl-2 levels). The levels of TNF-α (neuroinflammation), reactive oxygen species, and Brain-derived neurotrophic factor (BDNF) were also measured in ICH-subjected rats. GsMTx4, as a mechanosensitive channel blocker, and ANA-12, as a selective BDNF receptor blocker were employed as pharmacological agents. Results: Administration of GsMTx4 attenuated ICH-associated behavioral changes, preserved blood-brain barrier, prevented brain edema, and decreased apoptosis. GsMTx4 also decreased neuroinflammation and oxidative stress, while it increased the levels of BDNF. Moreover, administration of ANA-12 attenuated the neuroprotective effects of GsMTx4 suggesting that BDNF may be important in inducing neuroprotective effects of GsMTx4. Conclusion: GsMTx4 exerts neuroprotective effects in intracerebral hemorrhage-associated deleterious effects, which may be possibly due to an increase in BDNF levels along with a decrease in neuroinflammation and oxidative stress.
Keywords: Neuroinflammation; Oxidative stress; Intracerebral hemorrhage; Mechanosensitive channels; BDNF